Long-term exposure to diesel engine exhaust induces primary DNA damage: a population-based study - Duan, Huawei; Jia, Xiaowei; Zhai, Qingfeng; Ma, Lu; Wang, Shan; Huang, Chuanfeng; Wang, Haisheng; Niu, Yong; Li, Xue; Dai, Yufei; Yu, Shanfa; Gao, Weimin; et al. (Occupational and environmental medicine (London, England), 2016)
ObjectivesDiesel engine exhaust (DEE) is a ubiquitous environmental pollutant and is carcinogenic to humans. To seek early and sensitive biomarkers for prediction of adverse health effects, we analysed the components of DEE particles, and examined the genetic and oxidative damages in DEE-exposed workers.Methods101 male diesel engine testing workers who were constantly exposed to DEE and 106 matched controls were enrolled in the present study. The components of DEE were analysed, including fine particulate matter (PM2.5), element carbon (EC), nitrogen dioxide (NO2), sulfur dioxide (SO2) and polycyclic aromatic hydrocarbons (PAHs). Postshift urine samples were collected and analysed for 1-hydroxypyrene (1-OHP), an internal exposure marker for DEE. Levels of DNA strand breaks and oxidised purines, defined as formamidopyrimidine-DNA glycosylase (FPG) sites in leucocytes, were measured by medium throughput Comet assay. Urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) was also used to determine the level of oxidative stress.ResultsWe found higher levels of PM2.5, EC, NO2, SO2 and PAHs in the diesel engine testing workshop and significantly higher urinary 1-OHP concentrations in exposed subjects (p<0.001). Compared with controls, the levels of parameters in normal Comet and FPG-Comet assay were all significantly higher in DEE-exposed workers (p<0.001), and in a dose-dependent and time-dependent manner. There were no significant differences between DEE-exposed workers and controls in regard to leucocyte FPG sensitive sites and urinary 8-OHdG levels.ConclusionsThese findings suggest that DEE exposure mainly induces DNA damage, which might be used as an early biomarker for risk assessment of DEE exposure.